1971
DOI: 10.1002/ar.1091700405
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cells as the source of nuclei in muscles of growing rats

Abstract: The source of the new nuclei appearing during the growth of muscle fibers was examined in the tibialis anterior muscle of young Sherman rats (14-17 days of age) using radioautography at various intervals after a single injection of a small, non-toxic dose of 3H-thymidine ( 2 pCi/g body weight). Two techniques were employed: (1) labeled nuclei were detected in 1 $L thick radioautographs examined in the light microscope, and identified by simultaneous electron microscope examination of an adjacent section. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
481
1
5

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 920 publications
(505 citation statements)
references
References 13 publications
13
481
1
5
Order By: Relevance
“…Indeed, our assays of a reactivity with an antibody against myogenin cannot indicate whether myogenin in the cells is in its active form, whether other important molecules are present to participate in the myogenic activity of myogenin, and whether the myogenin-expressing cells developed the final block that will make the cells terminally differentiated (see reviews by Olson (1992Olson ( , 1993 and Weintraub (1993) regarding the role of phosphorylation and other regulatory proteins in modulating the function of the myogenic regulatory factors). The notion that only 50% of the satellite cell progeny eventually terminally differentiated is in agreement with the studies of Moss and Leblond (1971) who, analyzing [ 3 H]thymidine incorporation in growing rat muscle, suggested that following each division of satellite cells only 50% of the progeny can fuse with the fiber while the second cell can continue to proliferate. In the present study the satellite cell progeny which are not bound for terminal differentiation (expression of DEVmyosin) do not continue to proliferate either.…”
Section: Patterns Of Pcna Myod Myogenin αSmactin and Devmyosin Prsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, our assays of a reactivity with an antibody against myogenin cannot indicate whether myogenin in the cells is in its active form, whether other important molecules are present to participate in the myogenic activity of myogenin, and whether the myogenin-expressing cells developed the final block that will make the cells terminally differentiated (see reviews by Olson (1992Olson ( , 1993 and Weintraub (1993) regarding the role of phosphorylation and other regulatory proteins in modulating the function of the myogenic regulatory factors). The notion that only 50% of the satellite cell progeny eventually terminally differentiated is in agreement with the studies of Moss and Leblond (1971) who, analyzing [ 3 H]thymidine incorporation in growing rat muscle, suggested that following each division of satellite cells only 50% of the progeny can fuse with the fiber while the second cell can continue to proliferate. In the present study the satellite cell progeny which are not bound for terminal differentiation (expression of DEVmyosin) do not continue to proliferate either.…”
Section: Patterns Of Pcna Myod Myogenin αSmactin and Devmyosin Prsupporting
confidence: 89%
“…Individual myofibers become encased by a basement membrane during late embryogenesis and it is at that stage that the distinction of satellite cells by their morphology and location is first possible (reviewed in Grounds and Yablonka-Reuveni, 1993). In vivo studies analyzing the incorporation of [ 3 H]thymidine into satellite cell nuclei and, subsequently, into fiber nuclei, indicated that at least some of the satellite cells are proliferative in young animals, contributing additional nuclei to the fibers (Moss and Leblond, 1971). In the adult, satellite cells are mitotically quiescent but can reinitiate proliferative activity in response to injury, and their progeny eventually fuse into preexisting or new myofibers (Snow, 1977;Schultz et al, 1978Schultz et al, , 1985Carlson and Faulkner, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…LA of Group B rats can be ascribed to the expansion of their satellite cell pool (Table 3). Autoradiographic studies by Moss and Leblond (1971) showed mitotic activity within this pool to be the mechanism of postnatal increase in myonuclei. The above changes indicate the very wide morphological range across which the LA responds to manipulations of its trophic inputs.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of skeletal muscle to hypertrophy seems to be tightly coupled to the addition of myonuclei via satellite and myogenic cell fusion with existing myofibers (21). For example, the myonuclear domain of muscle fibers is maintained during muscle fiber hypertrophy due to postnatal growth (22)(23)(24), synergistic muscle ablation (25,26), stretch (27), or exercise (28,29). Muscle disuse atrophy due to a variety of experimental models results in the concurrent loss of myonuclei (14,21,(30)(31)(32)(33)(34).…”
Section: Mv-induced Alterations In Myonuclear Domainmentioning
confidence: 99%